Efeito anti-inflamatório da piperlongumina e modulação da expressão da proteína Anexina A1em modelo experimental de inflamação pulmonar - Santana, Monielle [UNIFESP] (2018)
Introduction: Smoking habit predisposes, among other conditions, to chronic obstructive pulmonary disease (COPD), with anti-inflammatory therapy being a therapeutic possibility. Among the mediators, with anti-inflammatory properties, we highlight the protein annexin A1 (AnxA1) and piperlongumine (PL), an alkaloid / amide of (Piper longum). The relationship between molecules has been explored by our research group and in silico analyzes show an interaction between AnxA1 and PL. With these considerations, it was important to understand this association in the prevention of the inflammatory process. Objectives: To evaluate the effect of the administration of PL and modulation of the endogenous AnxA1 in an experimental model of respiratory inflammation due to exposure to cigarette smoke. Material and methods: Male Balb/c mice were exposed to burning 10 commercial cigarettes, twice a day, for five weeks on their own equipment. To evaluate the efficacy of PL administration, three groups were investigated: control, exposed to untreated smoke and treated with PL (2.0mg / kg, three times per week, every other day). The animals were weighed and plethysmographic analyzes performed at the end of the exposure protocol. In the bronchoalveolar lavage (BAL) the inflammatory cells were evaluated and, in hemoglobin and glucose in the blood. Fragments of the lungs were processed for histopathological analyzes and expression of AnxA1, COX-2, NF-κβ and neutrophil elastase. Results: The plethysmography analysis revealed that the animals treated with PL maintained the frequency parameters and, pulmonary ventilation similar to controls, with a significant reduction in respiratory volume compared to untreated. However, final weight was reduced in both treated and untreated animals. PL decreased hemoglobin concentration, attenuated the reduction of glucose levels and reduced influx of lymphocytes, neutrophils and macrophages in BAL. Histopathologically, in animals without treatment there was infiltration of inflammatory cells, increase of the interalveolar septa and intra-alveolar spaces. While, PL administration structurally recovered lung tissues and, immunohistochemically, promoted the increase of the AnxA1 protein and reduction of COX-2, NF-kβ and neutrophil elastase. Conclusion: Together the results indicate that PL attenuates systemic and pulmonary inflammatory changes, in part modulating the expression of the endogenous protein AnxA1, which may represent a promising therapy in the prevention of the inflammatory process induced by exposure to cigarette smoke.